Estimating the Cost and Cost-effectiveness for Obstetric Fistula Repair in Hospitals in Uganda: a Low Income Country - Epiu, Isabella; Alia, Godfrey; Mukisa, John; Mohammed, Lamorde; Andreas, Kuznik (Health Policy and Planning, 2018)
In Africa, about 33 000 cases of obstetric fistula occur each year. Women with fistula experience debilitating incontinence of urine and/or faeces and are often socially ostracized. Worldwide, Uganda ranks third among countries with the highest burden of obstetric fistula. Obstetric fistula repair competes for scarce resources with other healthcare interventions in resource-limited settings, even though it is surgically efficacious. There is limited documentation of its cost-effectiveness in the most affected settings. We therefore sought to assess the cost-effectiveness of surgical intervention for obstetric fistula in Uganda so as to provide appropriate data for policy-makers to prioritize fistula repair and reduce women’s suffering in similarly burdened countries. We built a decision-analytic model from the perspective of Uganda’s National Health System to estimate the cost-effectiveness of vesico-vaginal and recto-vaginal fistula surgery vs a competing strategy of no surgery for Ugandan women with fistula. Long-term disability outcomes were assessed based on a lifetime Markov state-transition cohort and effectiveness of surgery. Surgical costs were estimated by micro-costing local Ugandan health resources. Disability weights associated with vesico-vaginal, recto-vaginal fistula and mortality rates among the general population in Uganda were based on published sources. The cost of providing fistula repair surgery in Uganda was estimated at $378 per procedure. For a hypothetical 20-year-old woman, surgery was estimated to decrease the lifetime disability burden from 8.53 DALYs to 1.51 DALYs, yielding a cost per DALY averted of $54. The results were robust to variations in model inputs in one-way and probabilistic sensitivity analyses. Surgery for obstetric fistula appears highly cost-effective in Uganda. In similar low-income countries, governments and non-governmental organizations need to prioritize training and strengthening surgical capacity to increase access to fistula surgical care, which would be an important step towards achieving universal health coverage.